The Sabbath world : glimpses of a different order of time - Shulevitz, Judith, 1963- (Random House, 2010)
In this erudite, elegantly written book, critic Judith Shulevitz weaves together histories of the Jewish and Christian sabbaths, speculations on the nature of time, and a rueful account of her personal struggle with the day. Whatever our faith or lack thereof, this rich and resonant meditation on the day of rest will remind us of the danger of letting time drive us heedlessly forward without ever stopping to reflect.